Pembuatan Lapisan Tipis TiO2 -DOPED Logam M (M= Ni, Cu dan Zn) Dan Apliksi Sifat Katalitiknya Pada Penjernihan Air Rawa Gambut - Willian, Nancy; Arif, Prof. Syukri (Jurnal Zarah, 2013)
Preparationof of TiO2-doped Metal M ( Ni, Zn and Cu) has been prepared using glass as substrate with dip-coating technique. Titanium isopropoksida (TIP, Ni(Oac)2 4 H2O, Zn (Oac)2 2 H2O dan Cu (Oac)2 were used as starting material with addition of dietanol amin (DEA) as additive in isopropanol solution. Film were prepared with various consentration of metal as 1, 3 and 5 mol %  with consentration of TIP in 0,5 M. Coating were prepared by immersion of glass substrate into solution and withdraw  speed of 20 cm/min. Coated glass were dried at 100 â 110o C and heated at 500o C the process were repeated for several time. The product were characterization by XRD and show that the appeared layer has structure of anatase. EDX analisis show that thin film have content of Ti, Ni and Cu. Crystallized zise were calculated with scherrer formula shown that various crystallize size are 12-21 nm. According to transformation effectivity of titania doped M in peat swam water shown that catalytic activity 34,40 â 53,71 for the irradiation during 24 hours.